Spectrophotometry As A Method To Estimate The Resistance Of Candida Albicans To Polyene Antibiotics - Arzumanian, Vera; Dzhadaeva, Anna; Chebotareva, Ekaterina; Lim, Vladimir; Avdeeva, Tatiana; Gorbunov, Nikita; Budanova, Elena; Vitaly, Rybakov; Zaborova, Victoria (Migration Letters, 2024)
Spectrophotometry method may be useful for estimation of Candida albicans resistance to polyene antibiotics. It is quantitative, exact and rapid (3-4 hours). Assessing the possibility of using this method to estimate the sensitivity of C. albicans to polyenes was the goal of this study. Yeast culture of C. albicans No. 927 was used. The traditional test for the sensitivity of yeast culture to polyenes was carried out using the method of two-fold microdilutions. The rapid estimation of the sensitivity of yeast cells to polyenes was carried out by the spectrophotometric method. The drug solution in saline was added to the cell suspension; the final cell concentration was 1010 CFU /ml. The control sample contained the saline and the yeast suspension. The sensitivity of yeast cells (i.e., drug antifungal activity) was calculated as the percentage of dye accumulated in the destroyed cells as compared to the control. The coefficient R was calculated using the formula: R = Aa / A. The fungicidal activity data (sensitiv[1]ity of yeast) at different concentrations of polyene is directly proportional to the concentration of polyenes. The introduction of another parameter R – the ratio between activity values at the nearest concentrations of polyenes – helps with understanding how to choose the minimum inhibitory concentration. Resulted values are correlated to MICs, which were estimated by microdilution method. With data obtained, it can be said that the spectrophotometric method can be used to quickly assess the values of the minimum inhibitory concentration of antifungal substances.